(untitled) (Research, Society and Development, 2020)
This article intends to open space for future research on the development of more effective leaders in Health Organizations, in the sense that when the health professional realizes that the actions of their leader are abusive, they can signal and even protect themselves from the effects that such actions can affect your performance and organizational well-being. Private health organizations (HO), like all profitable organizations, need to survive in the business world, not only offering quality services, but guaranteeing profits for the functioning of their activities. And in this scenario of great competition, modern questions arise about the possible styles or types of leadership that would be more appropriate to make health organizations achieve their goals, that is, it would be necessary to make organizations achieve their goals that the directions of the Health Organizations apply abusive supervision, because what has been observed, today, is that in the eagerness to earn profits, or to reach their goals, some HO leaders are very inclined to exercise abusive leadership. Therefore, the key point of the research will be to analyze the impacts of an abusive coordination on the performance of health professionals at work with a focus on “service provision”; such a study is of great relevance to the organizational world and, mainly, to health organizations (HO), as these are the main responsible for “excellence in the provision of health services to society”.